Analysis of Thermal Comfort of Office Buildings (Case Study: Hasanuddin University Rectorate Building) - Kamaruddin, Nurhayati Hayati; Hamzah, Baharuddin; Jamala, Nurul (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
Thermal comfort is one of the fundamental aspects of indoor environmental quality and it is closely related to occupant satisfaction and energy use in buildings. The purpose of this research was to analyze the thermal conditions of the student affairs rooms (Interest & Talent Room and Student Meeting room) at second floor and the academic and education rooms (Academic Meeting room, Academic Registration room, and Head of Education and Evaluation room) at seventh floor of Hasanuddin University rectorate building. This study used a quantitative method using a survey where the researcher asked several respondents about the level of thermal comfort of the room occupants when the volume of air conditioner (AC) is increased gradually every day at 18o C, 22o C, and 27o C. In addition, measurements were conducted using HOBO from 08.00 – 17.00 to obtain data in the form of air temperature, humidity, and air velocity in the room. At the same time, respondents were asked to fill out a questionnaire asking the level of comfort felt by the room occupants at that time. The results showed that the average air temperature at 18o C is 24.62o C, humidity is 63.108% and air velocity is 0.144 m/s. At a temperature of 22o C, the average air temperature is 24.78o C, humidity is 60.684%, and the air velocity is 0.142 m/s. At a temperature of 27o C, the average air temperature is 25.97o C, humidity is 64.022%, and the air velocity is 0.127 m/s. The results showed that the respondents felt ‚cold‘ when the volume was at 18o C, they felt 'comfortable' when the volume was at 22o C, and they felt ‚neutral‘ when the volume was at 27o C. In the end, temperatures of 22o C and 27o C can be used as a reference in the use of air conditioning temperatures in the room.